ANTIDIABETIC AND ENZYMATIC ANTIOXIDANT POTENTIAL FROM ETHANOLIC EXTRACTS OF LEAF AND FRUIT OF TRICHOSANTHES DIOICA AND LEAF OF CLITORIA TERNATEA ON DIABETIC RATS INDUCED BY STREPTOZOTOCIN - R, Kavitha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: To evaluate the antidiabetic and enzymatic antioxidant effects of ethanolic extracts of leaf and fruit of Trichosanthes dioica and leaf of Clitoria ternatea in streptozotocin (STZ)-induced diabetic rats. Methods: Male adult albino rats of Wistar strain equally divided into 11 groups of six rats each were assigned into non-diabetic and diabetic groups. Diabetes was induced in experimental animals by single dose intraperitoneal administration of STZ at a dose of 60 mg/kg body weight. Group I and II which served as non-diabetic and diabetic controls, respectively, received placebo treatment. The diabetic test Groups III to X were treated with either individual and combined ethanolic extracts of plant materials T. dioica and C. ternatea (200 and 400 mg/kg bw) and Group XI was treated with glibenclamide (600 Î¼g/kg bw) for 28 days consecutively. After completion of experimental duration, the animals were sacrificed and collected serum, liver, and kidney were used for the evaluating therapeutic effects on the STZ-induced diabetic rats. Results: The ethanolic extracts of T. dioica (leaf and fruit) and C. ternatea (leaf) and glibenclamide significantly reduced the levels of lipid peroxidation (LPO) and significantly increased the activities of enzymatic antioxidant markers superoxide dismutase, catalase, and glutathione peroxidase in serum, liver, and kidney of diabetic rats. Conclusions: From the present study, it can be concluded that the combined extract of T. dioica fruit and C. ternatea leaf was found to be more effective in treating diabetes and increased activities of enzymatic antioxidants in diabetic-treated rats substantiate that the investigated drugs do extend a clear protective action against LPO in STZ-induced diabetic rats.